Subjective Well-Being of School Students in Situation of Self-Identification - Pavlenko K.V; Bochaver A.A (Moscow State University of Psychology and Education, 2020)
This exploratory study aims to analyse the factors that influence subjective well-being of high school students. The purpose of the study is to formulate hypotheses about the impact of the situation of self-identification on the school students' subjective well-being. The research is based on 14 interviews with school students in 10th and 11th grades. These interviews showed how adolescents perceive the situation of transition from the status of schoolchildren to the status of school graduates, what aspects of this transition cause anxiety and stress, and what changes in the behavior and everyday life of schoolchildren are caused by the need to make educational and life choices. The results suggest that in schools with a highly competitive environment, in which students have higher educational aspirations, the stress from self-determination and planning for the future in adolescents is higher than in schools with a less competitive environment. The obtained data place the subjective well-being of the high schoolchild in a broader context of life path design and allow to formulate a hypothesis that it is the need to solve the age-related problem of self-determination that has a decisive influence on the experiences of adolescents of this age. Understanding how well-being is related to the characteristics of this transitional stage in adolescents' life, on the one hand, and social factors, on the other, creates the basis for further analysis: identifying risk groups of schoolchildren, studying and revising strategies to improve their well-being.